Red blood cell deformability as a predictor of anemia in severe falciparum malaria. - Dondorp, A; Angus, B; Chotivanich, K; Silamut, K; Ruangveerayuth, R; Hardeman, MR; Kager, P; Vreeken, J; White, N (1999)
Decreased erythropoiesis and increased clearance of both parasitized and noninfected erythrocytes both contribute to the pathogenesis of anemia in falciparum malaria. Erythrocytes with reduced deformability are more likely to be cleared from the circulation by the spleen, a process that is augmented in acute malaria. Using a laser diffraction technique, we measured red blood cell (RBC) deformability over a range of shear stresses and related this to the severity of anemia in 36 adults with severe falciparum malaria. The RBC deformability at a high shear stress of 30 Pa, similar to that encountered in the splenic sinusoids, showed a significant positive correlation with the nadir in hemoglobin concentration during hospitalization (r = 0.49, P < 0.002). Exclusion of five patients with microcytic anemia strengthened this relationship (r = 0.64, P < 0.001). Reduction in RBC deformability resulted mainly from changes in unparasitized erythrocytes. Reduced deformability of uninfected erythrocytes at high shear stresses and subsequent splenic removal of these cells may be an important contributor to the anemia of severe malaria.